Pembangunan Berkelanjutan sebagai Proyek Sosial: Kritik Humaniora terhadap Paradigma Pembangunan Modern - Pratama, Ahmad Fauzan; Rahmawati, Siti; Putra, Rizky Maulana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Sustainable development is often positioned as a normative solution to the multidimensional crises generated by the modern development paradigm. However, numerous studies in the humanities and social sciences argue that sustainable development is not merely a technocratic concept, but a social project embedded with values, interests, and power relations. This article aims to analyze sustainable development as a social project through a humanistic critique of the modern development paradigm. This study employs a qualitative approach using a systematic literature review of key works in the humanities, social philosophy, and sustainable development theory. The findings reveal that the modern development paradigm is largely reductionist, anthropocentric, and growth-oriented, thereby failing to address social inequality, ecological crises, and cultural diversity. Humanistic perspectives offer a more holistic alternative by emphasizing ethical, cultural, historical, and decolonial dimensions of sustainable development. In conclusion, sustainable development should be understood as a transformative social project that requires fundamental changes in values, institutions, and development practices rather than mere technical adjustments within modernity.